2016
DOI: 10.1097/bpb.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Posterolaterally displaced and flexion-type supracondylar fractures are associated with a higher risk of open reduction

Abstract: Objective To identify factors predictive of the risk of conversion from closed to open reduction. Methods ICD-9 codes were used to identify completely displaced pediatric supracondylar humerus fractures that underwent planned closed reduction and percutaneous pinning. Clinical and radiographic variables were retrospectively collected. Results Compared to posterior extension fractures, flexion [Risk Ratio (RR): 34.1, 95% CI: 8.1 to 143.6, p<0.0001] and posterolateral extension [RR: 6.0, 95% CI: 1.3 to 27.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
15
1
1
Order By: Relevance
“…These circumstances also make these fractures more unstable and prone to open reduction [8,11,18]. Many authors support the view that family members should be informed in these situations that the likelihood of open reduction is higher [8,11,19]. Novais et al tried to identify factors predictive of conversion from closed reduction to open reduction and found that flexion-type fractures were significantly more likely to undergo this conversion [19].…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances also make these fractures more unstable and prone to open reduction [8,11,18]. Many authors support the view that family members should be informed in these situations that the likelihood of open reduction is higher [8,11,19]. Novais et al tried to identify factors predictive of conversion from closed reduction to open reduction and found that flexion-type fractures were significantly more likely to undergo this conversion [19].…”
Section: Discussionmentioning
confidence: 99%
“…The location of fracture displacement (posteromedial or posterolateral) did not change fluoroscopy or operative times. Novais et al recently found that posterolaterally displaced supracondylar fractures were more likely to be converted to open reduction, 13 but no patient in our series required ORIF, nor were there any iatrogenic type 4 supracondylar fractures, which may reflect surgeon experience.…”
Section: Discussionmentioning
confidence: 48%
“…O cirurgião deve estar atento à maior incidência de lesão nervosa e necessidade de redução aberta nessas fraturas. 12,41,46,47 As fraturas irredutíveis podem ser abordadas por via anteromedial, medial, ou posterior, preservando o periósteo anterior íntegro e permitindo a visualização direta do nervo ulnar. 4,46 Complicações Perda de redução A perda de redução ocorre em torno de 4% dos casos, sendo sua principal causa a fixação inadequada.…”
Section: Métodos De Fixaçãounclassified
“…The surgeon must be aware of the greater incidence of nerve damage and the need for open reduction in these fractures. 12 41 46 47 Irreducible fractures can be addressed anteromedially, medially, or posteriorly, preserving the intact anterior periosteum and allowing direct visualization of the ulnar nerve. 4 46 …”
Section: Treatmentmentioning
confidence: 99%